Momoridica charantia and fermented Momoridica charantia with Leuconostoc mesenteroides MKSR change intestinal microbial diversity indices and compositions in high-fat and high-cholesterol diet-fed C57BL/6 male mice - Heewon Moon; Kangwook Lee; Jung-Heun Ha; Na Yeun Kim; Hyo Ri Shin; Tae Jin Cho; Nam Su Oh; Jinbong Park; Jingsi Tang; Jae Kyeom Kim; Misook Kim (Frontiers in Veterinary Science)
IntroductionThis study explores the impact of 4% Momordica charantia (MC) and 4% fermented Momordica charantia (FMC) on gut microbiota and obesity-related health outcomes in male C57BL/6 mice, a model relevant to veterinary sciences for understanding metabolic and gut health disorders in animals.MethodsMice were assigned to four dietary regimens, including control, high-fat and high-cholesterol diet (POS), POS with 4% MC, and POS with 4% FMC (fermented with Leuconostoc mesenteroides MKSR) over 12 weeks. Fecal samples were collected for 16S rRNA sequencing to evaluate microbial diversity and composition, key factors influencing animal health.ResultsBoth MC and FMC groups exhibited significant alterations in gut microbial communities, with FMC inducing a distinct shift in beta diversity indices. Changes in microbial taxa such as Bacteroidetes, Verrucomicrobia, and Firmicutes were observed, along with enhancement in the ‘L-glutamate and L-glutamine biosynthesis’ pathway. These shifts were associated with reduced body weight gain and liver weights.DiscussionThe findings suggest that MC and FMC have potential benefits for managing diet-induced metabolic disorders and protecting against obesity by modulating gut microbiota and improving gut metabolism.